Disease and democracy: political regimes and countries responsiveness to COVID-19 - Chen, C; Frey, CB; Presidente, G (Elsevier, 2023)
A widely held belief is that autocratic governments have been more effective in reducing the movement of people to curb the spread of COVID-19. Using daily information on lockdown measures and geographic mobility across more than 130 countries, we find that autocratic regimes have indeed imposed more stringent lockdowns and relied more on contact tracing. However, we find no evidence that autocratic governments were more effective in reducing travel, and evidence to the contrary: compliance with the lockdown measures taken was higher in countries with democratically accountable governments. Exploring a host of potential mechanisms, we provide suggestive evidence that democratic institutions are associated with attitudes that support collective action, such as mounting a coordinated response to a pandemic.